PENGARUH INFLASI, HARGA EMAS DAN JUMLAH NASABAH TERHADAP PENYALURAN PEMBIAYAAN AR-RAHN PADA PT PEGADAIAN SYARIAH UNIT GEUDONG - Hamdani Hamdani; Lianti Lianti; Fany Dasari (Politeknik Negeri Lhokseumawe, 2020)
Abstract: The purpose of this research is to determine how much inflation, gold price and number of customers on lending financing ar-rahn in Pegadaian Syariah Unit Geudong. This research is carried out by collecting secondary data which are found from the annual report of PT Pegadaian Syariah Unit Geudong and website of Bank Indonesia for period January 2016 to December 2018. The method used to analyze the relationship between independent variables with dependent variable is multiple linear regression method and classical assumption test. This research is a quantitative research by conducting quantitative data analysis. Technique of collecting data of this research is by collecting secondary data which have been finished. The result from this research shows that inflation, gold price and number of customers have significant influence on lending financing ar- rahn simultancously. gold price and number of customers influence to lending financing Ar-Rahn partially. The result is expected to be beneficial to Pegadaian Syariah, especially PT Pegadaian Syariah Unit Geudong in order to improve performance in the future.Keyword: Inflation , Gold Price , Number of Customers and Lend Financing of Ar-rahn